Pulmonary hypertension diagnosed by echocardiography during idiopathic myelofibrosis. A case report and a brief review of the literature - Perrone Claudio; Cartolari Roberto; Lupi Beatrice; Morelli Sergio (Multidisciplinary Respiratory Medicine, 2010)
Abstract Idiopathic myelofibrosis is a rare chronic myeloproliferative disease leading to extramedullary hematopoiesis (myeloid metaplasia) with splenomegaly. The liver and less frequently other organs including the lung can be involved, therefore portal hypertension is relatively common. Pulmonary hypertension (PH) is only occasionally reported, although recent studies have suggested an association between PH and myeloproliferative disorders. We present a case of PH diagnosis by echocardiography in a patient affected by idiopathic myelofibrosis with portal hypertension.